The Effect of Calcium Hydroxide Particle Size on the Viability of NIH3T3 Fibroblast Cells - Atia Nurul Sidiqa; Maysa Nursaena; Myrna Nurlatifah Zakaria (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Calcium hydroxide [Ca(OH)₂] is a widely used intracanal medicament due to its antimicrobial properties and its ability to stimulate hard tissue formation. Ca(OH)₂ plays a crucial role in endodontic therapy, primarily for its antimicrobial properties and its potential to facilitate reparative dentin formation. Its cytotoxic effects, particularly in relation to particle size, require in-depth investigation. This study aims to evaluate the cytotoxicity of calcium hydroxide with varying particle sizes on cultured fibroblast cells, thus providing insights into the implications of particle size on the biological responses elicited by calcium hydroxide. Material and Methods: This study was an in vitro experimental research aimed to evaluate the effect of Ca(OH)2 particle size on the viability of NIH3T3 fibroblast cells. Three forms of Ca(OH)2 were used: nanoparticles, microparticles, and commercial Ca(OH)2 as the positive control. Each sample was mixed with distilled water to form a paste and applied to cell cultures, while untreated cells served as the negative control. Cytotoxicity was assessed using the MTT assay after 24 hours of exposure, and cell viability was calculated relative to the control. Data were analyzed using the Kruskal Wallis and Mann Whitney tests with a significance level of α = 0.05. Results and Discussions: The nanoparticle Ca(OH)2 group showed the lowest cell viability (1.8%), which was significantly lower than that of the microparticle group (3.0%) and the commercial Ca(OH)2 group (5.0%) (p = 0.1). All Ca(OH)2 groups exhibited a high level of cytotoxicity, with cell viability below 20%, categorized as highly toxic. These results indicate that nanoparticle Ca(OH)2 may increase the risk of cellular toxicity. Conclusion: These findings emphasize the importance of considering particle size in the use of Ca(OH)2 as an intracanal medicament. Further biocompatibility evaluations are required to balance its antibacterial effectiveness with the safety of surrounding tissues.